Slow Physical Growth, Delayed Reflex Ontogeny, and Permanent Behavioral as Well as Cognitive Impairments in Rats Following Intra-generational Protein Malnutrition - Naik, Aijaz A.; Patro, Ishan K.; Patro, Nisha (Frontiers in Neuroscience, 2015)
Environmental stressors including protein malnutrition (PMN) during pre-, neo- and post-natal age have been documented to affect cognitive development and cause increased susceptibility to neuropsychiatric disorders. Most studies have addressed either of the three windows and that does not emulate the clinical conditions of intra-uterine growth restriction (IUGR). Such data fail to provide a complete picture of the behavioral alterations in the F1 generation. The present study thus addresses the larger window from gestation to F1 generation, a new model of intra-generational PMN. Naive Sprague Dawley (SD) dams pre-gestationally switched to LP (8% protein) or HP (20% protein) diets for 45 days were bred and maintained throughout gestation on same diets. Pups born (HP/LP dams) were maintained on the respective diets post-weaningly. The present study aimed to show the sex specific differences in the neurobehavioral evolution and behavioral phenotype of the HP/LP F1 generation pups. A battery of neurodevelopmental reflex tests, behavioral (Open field and forelimb gripstrength test), and cognitive [Elevated plus maze (EPM) and Morris water maze (MWM)] assays were performed. A decelerated growth curve with significantly restricted body and brain weight, delays in apparition of neuro-reflexes and poor performance in the LP group rats was recorded. Intra-generational PMN induced poor habituation-with-time in novel environment exploration, low anxiety and hyperactive like profile in open field test in young and adult rats. The study revealed poor forelimb neuromuscular strength in LP F1 pups till adulthood. Group occupancy plots in MWM test revealed hyperactivity with poor learning, impaired memory retention and integration, thus modeling the signs of early onset Alzehemier phenotype. In addition, a gender specific effect of LP diet with severity in males and favoring female sex was also noticed.